Aerosol delivery during spontaneous breathing with different types of nebulizers- in vitro/ex vivo models evaluation. (February 2018) - Lin, Hui-Ling; Fang, Tien-Pei; Cho, Hui-Sun; Wan, Gwo-Hwa; Hsieh, Meng-Jer; Fink, James B.
Abstract: Background: Nebulizers for spontaneous breathing have been evaluated through different study designs. There are limitations in simulated bench models related to patient and nebulizer factors. The aim of this study was to determine the correlation of inhaled drug mass between in vitro and ex vivo studies by testing aerosol deposition of various types of nebulizers. Methods: Ten healthy subjects were recruited to receive aerosol therapy with five nebulizers in random order: 1) a jet nebulizer (JN); 2) a breath-enhanced nebulizer (BEN); 3) a manually triggered nebulizer (MTN), 4) a breath-actuated nebulizer (BAN), and 5) a vibrating mesh nebulizer (VMN) with valved-adapter. A unit dose of salbutamol containing 5 mg in 2.5 mL was placed into the nebulizer and administered for 10 min. For the ex vivo study, minute ventilation of healthy subjects was recorded for 1 min. For the in vitro study a breathing simulator was utilized with adult breathing patterns. Aerosolized drug from the nebulizers and the accessory tubes was captured using inspiratory and expiratory collecting filters. Captured drug was eluted, measured and expressed as inhaled and exhaled mass using spectrophotometry at a wavelength of 276 nm. Results: 10 healthy subjects were recruited, aged 20.8 ± 0.7 years old, with a mean height of 166.2 ± 9.2 cm and weight of 64.7 ± 12.4 kg. There was no significant difference in the inhaled drug dose between the JN and BEN (15.0 ± 1.94% and 17.74 ± 2.65%, respectively, p = .763), yet the inhaled doses were lower than the other three nebulizers ( p < .001). The VMN delivered greater inhaled dose than the other four nebulizers ( p < .01). The respiratory rate of the cohorts was significantly correlated with the inhaled drug dose. For the in vitro model, the JN delivered a lower inhaled dose (11.6 ± 1.6, p < .001) than the other nebulizers, whereas the MTN and BAN deposited significantly lower exhaled doses (1.7 ± 0.4 and 2.7 ± 0.2, respectively, p < .001). The VMN demonstrated a greater drug dose with the in vitro study than the ex vivo model (44.0 ± 0.9% and 35.5 ± 6.3% respectively, p = .003), whereas the JN in the ex vivo model resulted in a greater inhaled drug dose (15.0 ± 1.9% for ex vivo vs 11.6 ± 1.6% for in vitro, p = .008). Conclusions: These in vitro/ex vivo model comparisons of nebulizers performance indicated that breath-related nebulizers can be estimated using an in vitro model; however, the JN and VMN delivered inhaled drug mass differed between models. There was a significant correlation between respiratory rate and inhaled mass, and the inhaled drug dose generated by VMN correlated with minute ventilation. This study demonstrated that the VMN produced greater inhaled drug dose and lowest residual dose, whereas the BEN, BAN, and MTN produced lower exhaled drug dose in both in vitro and ex vivo models.